Relationship Between Illness History, Exclusive Breastfeeding History, Food Consumption Patterns With Nutritional Status in Toddlers in The Working Area of Puskesmas Sikumana Kupang City - Lawa Djo, Victor Imanuel; Picauly, Intje; Laga Nur, Marselinus (Jurnal Pangan Gizi dan Kesehatan, 2026)
Background: Factors that cause toddlers to experience malnutrition problems are toddlers who have experienced illness where the body has decreased appetite, toddlers do not get exclusive breastfeeding, poor daily food consumption patterns. Objectives: This study aims to determine the relationship of illness history, exclusive breastfeeding history, food consumption patterns with nutritional status in toddlers in the Sikumana Health Center working area of Kupang City. Methods : This type of research is an analytic survey with a cross sectional study approach. This study was conducted in the working area of Sikumana Health Center in Kupang City in March-April 2025. The population of this study were all toddlers aged 7-12 months in the working area of Sikumana Health Center, Kupang City. Sample determination using the Slovin formula with a sample size of 99 respondents. The statistical test used Chi-square test analysis with a=0.05. Results: The results showed that the variable history of illness (p-value=0.000), exclusive breastfeeding history (p-value=0.000), food consumption patterns (p-value=0.000) were associated with the nutritional status of toddlers in the Sikumana Health Center working area in Kupang City. Conclusions: It is expected that parents of toddlers pay more attention to toddlers so as not to get sick and pay attention to their food consumption patterns every day and add information about the importance of exclusive breastfeeding to prevent malnutrition problems in toddlers.